Alternatif Bahan Bakar Maritim Ramah Lingkungan: Tinjauan - Meilinda, Reza; Ningsih, Putri Amelia; Anggraini, Dian; Pardi, Hilfi (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2024)
Indonesia is an archipelagic country with an ocean area wider than land. Indonesia's ocean areas contain many maritime activities, one of which is shipping and trade. This activity causes a lot of domestic and foreign transportation to pass through Indonesia's maritime areas. It is not uncommon for domestic and international sea transportation to discharge exhaust emissions from their fuel onto the sea surface, causing marine damage. This article was created with the aim of summarizing previous research to make it easier for readers and to find out the appropriate types of maritime chemical fuels, combustion and exhaust emissions, as well as reducing pollution from combustion. The review of studies uses a comparative approach, collecting sources from Google Scholar and PubMed databases, as well as national and international publications. The research results show that liquefied natural gas (LNG) and hydrogen are good candidates to replace chemical fuels because they are both sulfur-free.